2014
DOI: 10.1002/ajmg.a.36872
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion of 12q24.31: Report of a girl with intellectual disability, stereotypies, seizures and facial dysmorphisms

Abstract: We provide a detailed clinical and molecular characterization of an 11-year-old female patient presenting with neurodevelopmental delay (NDD), intellectual disability (ID), seizures, stereotypies and dysmorphic features. Chromosomal microarrays analysis (CMA) detected a small, rare de novo deletion on chromosome 12q24.31 encompassing 31 protein-coding RefSeq genes and a microRNA. Phenotypic comparison with molecularly well-defined cases previously reported in the literature harboring an overlapping 12q24.31 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
1
17
1
1
Order By: Relevance
“…In humans, microdeletions and microduplications of CNTN6 have been reported in patients with DD, ID, speech and language delays, atypical autism suggesting that under- and overexpression of this gene is responsible for the observed phenotypes [ 16 ]. In agreement with Shoukier et al [ 6 ], we cannot exclude the existence of a position effect on the CNTN6 gene, as already reported for others copy number variations [ 17 , 18 ]. Obviously, this observation need to be elucidated by further gene expression studies either on experimental in vivo animal models or on diagnostic material.…”
Section: Discussionsupporting
confidence: 91%
“…In humans, microdeletions and microduplications of CNTN6 have been reported in patients with DD, ID, speech and language delays, atypical autism suggesting that under- and overexpression of this gene is responsible for the observed phenotypes [ 16 ]. In agreement with Shoukier et al [ 6 ], we cannot exclude the existence of a position effect on the CNTN6 gene, as already reported for others copy number variations [ 17 , 18 ]. Obviously, this observation need to be elucidated by further gene expression studies either on experimental in vivo animal models or on diagnostic material.…”
Section: Discussionsupporting
confidence: 91%
“…Interesting to note, in one patient (DECIPHER 333097) the deletion did not encompass any of the two mentioned genes ( CELSR1 and ATXN10 ) although he showed NDDs and seizure. Given that deletion is very close to CELSR1 , we cannot exclude the existence of a position effect on the genes located in the neighboring regions, as already reported for others copy number variations (Ibn‐Salem et al, ; Kleinjan & van Heyningen, ; Palumbo et al, ), or the influence of polymorphisms external to the deleted region that contribute to penetrance. Obviously, this observation need to be elucidated by further studies either on experimental in vivo animal models or on diagnostic material.…”
Section: Discussionmentioning
confidence: 89%
“…There is a very similar regulatory cascade in leukemia cells, where transcription factor NFkB recruits the MLL1 histone methyltransferase complex to activate NFkB target genes after TNF treatment 41 . It was previously reported that SETD1B is a possible causative gene for the pathogenesis of the 12q24.3 deletion syndrome 42,43 . In this regard patients with de novo SETD1B mutations showed signs of epilepsy, developmental delay, intellectual disability, and autism 44 .…”
Section: Discussionmentioning
confidence: 99%